Identification of the initiation sequence for viral-strand DNA synthesis of wheat dwarf virus. - Heyraud, F (1993)
The intergenic region of the circular single-stranded DNA genome of geminiviruses contains a sequence potentially able to fold into a stem-loop structure. This sequence has been reported to be involved in viral replication by serving as the origin for rolling-circle replication. However, in wheat dwarf virus (WDV) a deletion of 128 bp, removing this sequence, surprisingly does not prevent de novo viral DNA synthesis, but instead abrogates the processing of replicative intermediates into monomeric genomes. This deletion mutant permitted us to study the initiation of viral-strand DNA synthesis independently from its termination and also to identify the sequence within which rolling-circle DNA replication of WDV begins. We have mapped the initiation site of replication to a pentanucleotide, TACCC, a sequence that occurs twice in the large intergenic region of WDV: it is found in the right half of the stem-loop sequence and again 170 bases upstream where it is part of a 15 nucleotide sequence highly homologous to the right half of the stem-loop sequence. Here we show that viral-strand DNA synthesis efficiently initiates at both sequences.